Do action movies enrich vocabulary mastery? Students’ perceptions - Maharani, Mega Mulianing; Azizatun Ni'mah; Hartono, Hartono; Ekaningsih, Nur (Indonesian Journal of Education and Pedagogy, 2025)
The acquisition and understanding of vocabulary play an important role in language learning because they are essential for effective communication. Lack of motivation is a challenge for many students. Using action movies is the solution to build their motivation to enrich their vocabulary. Through this research, researchers explore the students' perceptions regarding the use of action movies to enrich vocabulary. A qualitative descriptive approach is used. The data are collected through semi-structured interviews addressed to 15 students in one of the English Courses. They are selected purposively and asked to share their experiences in using action movies to enrich their vocabulary. The results show that action movies were argued to be able to enrich the students’ motivation and interest in learning vocabulary; show effectiveness in enriching vocabulary mastery, solve challenges in understanding vocabulary through action movies, and show a comparison with other genres.